First Investigation of OqxAB nd Plasmid-mediated Quinolone Resistance Determinant Qnr Genes in Stenotrophomonas maltophilia Isolates - Yeliz TANRIVERDİ ÇAYCI; İlknur BIYIK; Asuman BİRİNCİ (Mediterranean Journal of Infection, Microbes and Antimicrobials, 2021)
Introduction: Stenotrophomonas maltophilia, a non-fermentative bacterium, predominantly causes opportunistic infections in immunocompromised individuals and those receiving long-term, large-dose, broad spectrum antimicrobial agents. It is inherently resistant to most of the available antimicrobial agents. Trimethoprim-sulfamethoxazole (TMP/SMX), ceftazidime (CAZ), and levofloxacin (LVX) are the drugs of choice used for the infection treatment. The study aims to investigate the presence of plasmid-mediated quinolone resistance determinants of QnrA, QnrB, QnrC, QnrD, QnrS, and OqxAB genes in S. maltophilia isolates. Materials and Methods: A total of 122 S. maltophilia isolates from various clinical specimens were tested in the study. The susceptibility of TMP/SMX and LVX was determined by disk diffusion method. The minimum inhibitory concentration value of CAZ was determined by the gradient diffusion test. Qnr (A, B, C, S, D) determinants and OqxAB were investigated using multiplex polymerase chain reaction. OqxA was investigated in the isolates and the presence of OqxB in OqxA-positive isolates. Results: Five (4%) of the S. maltophilia isolates were resistant to TMP/SMX. Levofloxacin and CAZ resistances were determined as 6.5% and 56.5%, respectively. QnrS was detected in two of the isolates, and OqxA gene was found in three isolates. However, these isolates were not OqxB positive. One of these three positive isolates has been previously found to be QnrS-positive. Conclusion: In our study, QnrS was detected in two and OqxA gene in three of the S. maltophilia isolates.